Process of Infection with Bacteriophage φX174: XXXVI. Measurement of Virus-Specific Proteins During a Normal Cycle of Infection - Mayol, Robert F. (1970)
Double-labeling techniques in which (14)C-labeled, φX174-infected cells and (3)H-labeled, uninfected cells were used permitted the identification of the virus-specific proteins after separation by sodium dodecyl sulfate-polyacrylamide gel electrophoresis without prior inhibition of host-cell protein synthesis by ultraviolet irradiation. It was also possible to detect previously undescribed components of high molecular weight which may represent induced host proteins. The gel regions specifically corresponding to cistron II protein and the chloramphenicol-resistant VI protein were identified, and a third new, small peak of unknown origin was detected. Studies of the rate of synthesis of virus-specific proteins at various times after infection indicated that the product of cistron I (lysis) is made only late in infection, but the other proteins seemed to be synthesized at the same relative rates throughout infection (although in different amounts). Studies of the proteins obtained from uniformly labeled φX virus particles indicated that all of the spikes are identical and allowed a formulation of the structure of the phage capsid.